Transformasi Sistem Pemasyarakatan di Indonesia: Analisis Kritis terhadap Implementasi Pembebasan Bersyarat dan Tantangan dalam Reintegrasi Narapidana ke Masyarakat - Myharto, Wiend Sakti; Nugroho, Taufiq Ardi; Sadat, Anwar (PT Elaborium Elevasi Indonesia, 2024)
The law is a response to society's need for rules to ensure justice. The fulfillment of citizens' rights must be carried out through appropriate legal procedures. This maintains public trust in the government. Violations of the law are subject to sanctions, according to the act. The goal is to prevent the perpetrator from repeating his actions. In criminal law, sanctions range from imprisonment to asset confiscation. Corrections are now the main concept of inmate development. The adoption of a qualitative approach based on normative legal methods was carried out to understand the legal structure and its application. Data was collected from written documents, interviews, and participant observation. The focus is given to literature relating to legal regulation. The correctional system is oriented towards Pancasila values and involves various parties in developing prisoners. The coaching program in correctional institutions aims to build the character and independence of prisoners. Parole, as one of the prisoners' rights, supports development outside the correctional institution. However, there are irregularities in granting parole, including extortion in prisons. Supposedly, parole is granted based on the principle of justice, but in reality, there is an imbalance in its implementation.